Generalized fronts propagation on weighted graphs - Desquesnes, Xavier; Elmoataz, Abderrahim; Lézoray, Olivier (Proceedings of the Conference Algoritmy, 2015)
In this paper, we propose a general formulation and an algorithm for simultaneous propagation of several fronts evolving on a weighted graph. This formulation is an adaptation of the continuous level set formulation for front propagation and uses a Partial dierence Equations (PdEs) framework. The proposed algorithm is a graph-based version of the Fast Marching algorithm that allows simultaneous inward or outward propagation of several fronts. Experiments illustrate the behavior of the algorithm and show some application results on several types of data.